Gaze correction for videoconferencing - Lim, Kim Seah. (2009)
One pressing problem of using webcams is the off-alignment of the camera with respect to a user’s gaze. This Final Year Project (FYP) will attempt to synthesize a gaze corrected (cyclopean) view using two stereo and synchronized webcams. The two webcams will be used to capture two separate live video streams which will be processed in an open-source computer vision software, OpenCV. A technique based on “Dynamic Programming” (DP) is employed to derive a minimum cost path along every scanline. Application of this technique will lead to dense stereo correspondences between the frame (an instance of a video stream) pair. For the purpose of this project, dynamic programming can be implemented in two ways: Conventional 3-move DP or the new and improved 4-move, 4-plane DP by Criminisi [1]. This FYP will implement both DP ways to compare and generate novel synthesized cyclopean view and most importantly, validate the observations made by Criminisi’s improved 4-move 4-plane algorithm. The suitability for implementation commercially will also be evaluated and discussed.